β-Caryophyllene and Statins in Bone Fracture Healing – A Narrative Review - Marom H; Khan MA; Darvish N; Tornetta III P; Khoury A; Weil YA; Skelley NW; Allison DC; Meiron S; Ehrmann Barr T (Orthopedic Research and Reviews)
Hilik Marom,1,* Mansoor A Khan,1,* Nissim Darvish,2,* Paul Tornetta III,3,* Amal Khoury,4,* Yoram A Weil,5,* Nathan WM Skelley,6,* Daniel C Allison,7,* Sahar Meiron,2,* Tami Ehrmann Barr1,* 1R&D, OrthoTreat Ltd, Tel Aviv-Jaffa, Israel; 2Corporate Office, OrthoTreat Ltd, Tel Aviv-Jaffa, Israel; 3Department of Orthopaedic Surgery and Orthopaedic Trauma, Chobanian and Avedisian School of Medicine, Boston Medical Center, Boston, MA, USA; 4Division of Orthopaedic Surgery, Orthopaedic, and Reconstructive Trauma Surgery, Tel Aviv Sourasky Medical Center, Tel Aviv, Israel; 5Department of Orthopaedics, Hadassah Hebrew University Hospital, Jerusalem, Israel; 6Department of Orthopaedics, Sanford Health, Sioux Falls, SD, USA; 7Department of Orthopaedic Oncology, Cedars-Sinai Medical Center, Los Angeles, CA, USA*These authors contributed equally to this workCorrespondence: Tami Ehrmann Barr, Email drbarr@orthotreat.ioAbstract: Bone fractures are a leading cause of morbidity and healthcare expenditure globally. The complex healing process involves inflammation, cartilage formation, mineralization, and bone remodeling. Current treatments like immobilization, surgery, and bone grafting, though effective, pose significant challenges, such as prolonged recovery and high costs. Emerging therapies such as biological agents, pharmacological treatments, and physical stimulation techniques are also associated with high costs, side effects, and practical applicability limitations. There is a critical need for alternative therapies that are cost-effective, safe, and easy to use. Recent studies suggest the potential of β-caryophyllene (BCP) and statins in promoting bone healing. BCP, a naturally occurring anti-inflammatory and antioxidant compound found in essential oils, enhances osteoblast activity and inhibits osteoclastogenesis. Statins, known for their cholesterol-lowering effects, also promote bone formation and reduce bone resorption through multiple biochemical pathways. Both BCP and statins have shown promising results in preclinical studies, enhancing bone density and promoting fracture healing. This review explores the individual and potential synergistic effects of BCP and statins on bone fracture healing. It highlights the complementary mechanisms of these agents: BCP’s anti-inflammatory and osteogenic properties and statins’ ability to inhibit osteoclast activity and promote angiogenesis. Combining BCP and statins could offer a multifaceted approach to enhance fracture healing, reduce complications, and improve patient outcomes. While individual effects are supported preclinically, further studies investigating synergies, formulations, and clinical translation are needed to develop this promising novel therapeutic approach for improving fracture repair outcomes.Keywords: bone regeneration, fracture repair, osteoblast, osteogenesis, piezoelectric effect